Teenage Pregnancy in Indonesia: Determinants and Outcomes - Rati Purnama Sari; Verra Widhi Astuti (Universitas Aisyah Pringsewu, 2022)
This review aims to identify determinants and outcomes associated with teenage pregnancy in Indonesia. A search in PubMed, ScienceDirect, and google scholar databases in the last ten years (2011 to 2021) was conducted. The keywords were